PROTEKSI ARUS LEBIH PADA PENYULANG LENGUH (SKTM) DAN PENYULANG AUM (SUTM) - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2015)
In the distribution system generally has some disorder that consists of a short circuit between phase, three-phase, two-phase to ground, single phase to ground. It can result from this short circuit, which will cause an overcurrent / short-circuit current depends on the length of the existing relay adjustment in the outgoing feeder. In order for the distribution of electricity has a high quality and reliability, the electrical equipment must have protection from any form of interference that may cause interruption of service. This research will discuss the setting adjustment disorders relay single phase to ground, phase-to-phase disorders, as well as examination of the working time relay so we get a better understanding of the working time relay if the current disruption of the distribution system.